Kalanchoe ×hankeyi [= K. longiflora × K. sexangularis] (Crassulaceae subfam. Kalanchooideae), a new nothospecies from South Africa - Smith, Gideon F. (Phytotaxa, 2020)
In southern Africa, two species of Kalanchoe Adanson (1763: 248), K. longiflora Schlechter ex Wood (1903: plate 320) (Figure 1A) and K. sexangularis Brown (1913: 120) (Figure 1B), are extensively grown as groundcovers or accent plants. Both species thrive in open beds as well as in containers and have gained horticultural prominence, especially as result of their ability to flourish on little irrigation during times of drought. Kalanchoe sexangularis has bright red leaves when grown in exposed positions, while in similar positions K. longiflora has orange-infused, turquoise-coloured leaves. Vegetatively both species are of low to medium growth with plants reaching a height of about 0.5 m. When flowering maturity approaches, the central axis elongates significantly into flat-topped, thyrsoid inflorescences that overtop the pseudo-rosettes. The flowers of both K. longiflora (Smith & Figueiredo 2017) and K. sexangularis (Figueiredo et al. 2016) have bright yellowish green corolla tubes and golden yellow corolla lobes.